2012
DOI: 10.1097/ta.0b013e3182463b45
|View full text |Cite
|
Sign up to set email alerts
|

Screw- versus plate-fixation strength of acetabular anterior column fractures

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 26 publications
2
59
0
1
Order By: Relevance
“…However, the results of the current study suggest that a more rigid fixation is possible by Kocher-Langenbeck approach for transverse fractures. Gras et al have recently reported screw fixation of the anterior column to be equivalent to anterior column plating in fixation strength [16]. This was in concurrence with our study that screw fixation of the anterior column was comparable with anterior column plating.…”
Section: Discussionsupporting
confidence: 94%
“…However, the results of the current study suggest that a more rigid fixation is possible by Kocher-Langenbeck approach for transverse fractures. Gras et al have recently reported screw fixation of the anterior column to be equivalent to anterior column plating in fixation strength [16]. This was in concurrence with our study that screw fixation of the anterior column was comparable with anterior column plating.…”
Section: Discussionsupporting
confidence: 94%
“…The recently described infraacetabular screw placement seems to be a promising alternative to increase fracture fixation strength up to 50% by closing the periacetabular fixation frame as shown in two biomechanical studies [11,24]. In our clinical experience, the infraacetabular corridor of some patients is too narrow or has a bowing shape; this may exclude secure intraosseous screw placement.…”
Section: Introductionmentioning
confidence: 85%
“…methods underlining the necessity of stable osteosynthesis to prevent re-displacement of the QLP [6,24]. However, the lack of homogeneity in biomechanical test set-ups aggravates comparison under full weight-bearing conditions [6,7,10,17,22,24,33,36]. In particular no comparative biomechanical data has been made available regarding cages designed for primary THA which address displaced acetabular fractures in the elderly.…”
Section: Introductionmentioning
confidence: 99%